2011
DOI: 10.1111/j.1439-0531.2011.01873.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Assessment During Pregnancy in Goats – A Review

Abstract: Contents Obstetric ultrasonography is the most common diagnostic approach used in veterinary reproduction because it is a simple, reliable and non‐invasive imaging technique. With advances in ultrasonography of small ruminants, assessment of pregnancy in goats is challenging for accurately managing reproduction. This article presents an up‐to‐date review of the use of ultrasonography in pregnancy for the diagnosis and evaluation of intrauterine foetal growth in goats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
0
16
0
4
Order By: Relevance
“…It allows the performance of foetometry when crown rump length and BPD are not measurable, especially in the third trimester (4,11). In the present study, there was only one significant difference between the TD values of single and twin foetuses, on day 115 of pregnancy (P < 0.01).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It allows the performance of foetometry when crown rump length and BPD are not measurable, especially in the third trimester (4,11). In the present study, there was only one significant difference between the TD values of single and twin foetuses, on day 115 of pregnancy (P < 0.01).…”
Section: Discussionmentioning
confidence: 50%
“…The use of ultrasonography minimises the slaughter rate of pregnant animals, facilitates optimal feeding for ideal birth weight, and reduces feed cost in females carrying a singleton (1)(2)(3)(4). Moreover, the pregnant ewe model being used in numerous human biomedical studies and ultrasound examination of foetuses in the intrauterine environment emphasises the multidisciplinary importance of this method (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Animals with evidence of fetal non-viability (significant reduction of intrauterine fluid, absence of fetal heart beat, and absence of fetal movement) were administered 2 mL of dinoprost tromethamine (Lutalyse®, Zoetis Inc., Kalamazoo, MI, USA) and uterine contents were collected approximately 48 – 72 h later. Crown-rump lengths were determined on recovered fetuses to estimate gestational age of death based on a previously published equation (y = 24.42 + 0.39x) [28,29]. Fetuses were dissected to collect tissues including liver, heart, thymus, skin, brain, and placenta for VI and RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The main parameter of gestational age during the first three postconception weeks is uterine lumen diameter. As pregnancy advances, structures such as embryo/foetus, placentomes and amniotic fluid amount could be visualized and measured as well (Erdogan, 2012;Martinez, Bosch, & Bosch, 1998). The major part of researchers (Abdelghafar et al, 2011;Karen et al, 2009;Suguna et al, 2008) demonstrated a strong correlation (R 2 ≥ 0.90) between gestational age and crown-rump length (CRL), trunk diameter (TD) and biparietal diameter (BPD).…”
Section: Introductionmentioning
confidence: 99%